Versatile writer of contemporary tatar literature: zölfet hekim - Öztürk, Mehtap (Ahmet BURAN, 2021)
Zölfet Hekim is one of the most important and prominent name in the 20th century Tatar literature. In this article, the place of Zölfet Hekim in the Tatar literature, his works, his literary personality, the language and point of view he used in his works is emphasized. Zölfet, who is a writer, poet, drama master and vocal artist, reflected his feelings and thoughts in art, sometimes funny and satirical, sometimes realistically by observing life and people. He wrote many genres of stories and novels in mythological, psychological, comedy, drama history, fantastic and absurd styles.

Zölfet Hekim, XX. yüzyılın sonu ve XXI. yüzyılın başı Tatar Edebiyatının önde gelen isimlerinden birisidir. Makalede Zölfet Hekim’in Tatar Edebiyatındaki yeri, eserleri, edebî kişiliği, eserlerinde kullandığı üslup ve bakış açısı üzerinde durulmuştur. Yazar, şair, dram ustası ve ses sanatçısı olan Zölfet, hayatı ve insanları gözlemleyerek kimi zaman komik ve hicivli kimi zaman da gerçekçi bir biçimde duygularını ve düşüncelerini sanata yansıtmıştır. Mitolojik, psikolojik, komedi, dram, tarih, fantastik ve absürt tarzda pek çok türde hikâye ve roman yazmıştır.
ÇAĞDAŞ TATAR EDEBİYATINININ ÇOK YÖNLÜ YAZARI: ZÖLFET HEKİM
Keywords: Linguistics; Dilbilim